Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/6970578
|View full text |Cite
|
Sign up to set email alerts
|

Banhasasim‐Tang Ameliorates Spatial Memory by Suppressing Oxidative Stress through Regulation of ERK/p38 Signaling in Hippocampus of Mice

Abstract: Since ancient times, Banhasasim-tang (BHS) has been used to treat functional dyspepsia in East Asia. Here, we aimed to determine the protective action of BHS on hippocampal neurons against oxidative stress. We investigated the functional effect of BHS on a scopolamine-induced mouse model, and molecular analysis was performed in glutamate-induced HT22 cells. We observed that BHS administration ameliorated memory dysfunction in scopolamine-treated mice. BHS administration also increased neuronal survival and ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…CREB phosphorylation plays a regulatory role in neuronal growth, survival, and synaptic connectivity, further impacting the function of the hippocampus ( Lonze and Ginty, 2002 ). Specifically, CREB can control the synthesis of specific proteins, including brain-derived neurotrophic factor (BDNF), an important biological molecule for maintaining the normal function of neurons ( Pak et al, 2021 ; Lu et al, 2022 ). Further, previous studies found that BDNF plays an important regulatory role in neuron growth and differentiation by specifically binding to its receptor, tyrosine kinase receptor B (TrkB) in the hippocampus, meanwhile, the hormone level changes resulting from severe stress exposure have a regulatory effect on the BDNF/TrkB signaling pathway ( Notaras and van den Buuse, 2020 ; Camuso et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…CREB phosphorylation plays a regulatory role in neuronal growth, survival, and synaptic connectivity, further impacting the function of the hippocampus ( Lonze and Ginty, 2002 ). Specifically, CREB can control the synthesis of specific proteins, including brain-derived neurotrophic factor (BDNF), an important biological molecule for maintaining the normal function of neurons ( Pak et al, 2021 ; Lu et al, 2022 ). Further, previous studies found that BDNF plays an important regulatory role in neuron growth and differentiation by specifically binding to its receptor, tyrosine kinase receptor B (TrkB) in the hippocampus, meanwhile, the hormone level changes resulting from severe stress exposure have a regulatory effect on the BDNF/TrkB signaling pathway ( Notaras and van den Buuse, 2020 ; Camuso et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%